سلطة القاضي الإداري في توجيه أوامر للإدارة - شاوش, حميد; بورجيبة, آسيا (University of Eloued جامعة الوادي, 2018)
The power of the administrative judge to instruct the administration to implement his judicial rulings did not exist prior to the promulgation of Law No. 08_09, which contained the Civil and Administrative Procedures Law, except for some very limited orders. However, with the issuance of this law, The administration of the principle of legality, which did not raise the necessary attention in the Code of Civil Procedure and administrative former, which is one of the most important manifestations of "state law" to require respect for the general administration of laws, including the provisions of the judiciary, strengthening the status of the administrative judge as a result of recognition of the authority of the matter led to The transfer of justice from the theoretical to the practical, which contributed to the achievement of legal security by establishing the stability of legal centers.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: القاضي الإداري، الأوامر، التنفيذ; Administrative Judge, Orders, Execution